2011
DOI: 10.1634/theoncologist.2011-0079
|View full text |Cite
|
Sign up to set email alerts
|

Impact of New Chemotherapeutic and Targeted Agents on Survival in Stage IV Non-Small Cell Lung Cancer

Abstract: Purpose. Significant advances in the systemic management of metastatic non-small cell lung cancer (NSCLC) have occurred over the past decade, with options now including multiple lines of chemotherapy, epidermal growth factor receptor inhibitors, and antiangiogenic agents. Improvements in overall survival have been demonstrated in randomized controlled trials comparing these newer agents with best supportive care or standard therapy. This study examined uptake of these therapies in general practice and their im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
1
20
0
1
Order By: Relevance
“…Although chemotherapy utilization rates in our study appear low (25% in 2007 and 29% in 2011), they are consistent with rates reported in studies using data from the U.S. Surveillance, Epidemiology, and End Results database and Ontario databases 17,18 . They are notably lower than rates in studies conducted at a single institution the United States and a U.S.-based health maintenance organization; however, the latter studies also noted a correlation between socioeconomic status or access to insurance and rates of treatment 19,20 .…”
Section: Discussionsupporting
confidence: 90%
“…Although chemotherapy utilization rates in our study appear low (25% in 2007 and 29% in 2011), they are consistent with rates reported in studies using data from the U.S. Surveillance, Epidemiology, and End Results database and Ontario databases 17,18 . They are notably lower than rates in studies conducted at a single institution the United States and a U.S.-based health maintenance organization; however, the latter studies also noted a correlation between socioeconomic status or access to insurance and rates of treatment 19,20 .…”
Section: Discussionsupporting
confidence: 90%
“…The median survival duration of 3-5 months in our patients is similar to the median survival duration reported in patients with stage iv nsclc treated with best supportive care alone, and reflects a low rate of chemotherapy use in our cohort 33 . Some studies from British Columbia and Ontario suggest that, during a similar period, the proportion of stage iv nsclc patients who received chemotherapy increased to 35%-45% from less than 25% over time 33,34 . One Canadian study reports up to 50% administration of systemic therapy between 2009 and 2012 35 .…”
Section: Figurementioning
confidence: 99%
“…The majority of lung cancers are malignant carcinomas, and non-small cell lung cancer (NSCLC) accounts for >80% of these (2). Although advances in treatment have occurred in the past few years, the survival rate for patients with NSCLC remains at ~15% due to cancer metastasis and high recurrence rates (3). Therefore, it is necessary to further investigate the molecular mechanisms underlying the initiation of NSCLC development.…”
Section: Introductionmentioning
confidence: 99%